Comparative Genomic Analysis of Capsule-Producing Black Yeasts Exophiala dermatitidis and Exophiala spinifera, Potential Agents of Disseminated Mycoses - Song, Yinggai; da Silva, Nickolas Menezes; Weiss, Vinicius Almir; Vu, Duong; Moreno, Leandro F.; Vicente, Vania Aparecida; Li, Ruoyu; de Hoog, G. Sybren (Frontiers in Microbiology, 2020)
The two black yeasts Exophiala dermatitidis and Exophiala spinifera that are clinically considered as the most virulent species potentially causing disseminated infections are both producing extracellular capsule-like material, are compared. In this study, 10 genomes of E. spinifera and E. dermatitidis strains, including both clinical and environmental isolates, were selected based on phylogenetic analysis, physiology tests and virulence tests, sequenced on the Illumina MiSeq sequencer and annotated. Comparison of genome data were performed between intraspecific and interspecific strains. We found capsule-associated genes were however not consistently present in both species by the comparative genomics. The prevalent clinical species, E. dermatitidis, has small genomes containing significantly less virulence-associated genes than E. spinifera, and also than saprobic relatives. Gene OG0012246 and Myb-like DNA-binding domain and SANT/Myb domain, restricted to two strains from human brain, was shared with the neurotropic species Rhinocladiella mackenziei. This study indicated that different virulence profiles existed in the two capsule-producing black yeasts, and the absence of consistent virulence-associated profiles supports the hypothesis that black yeasts are opportunists rather than primary pathogens. The results also provide the key virulence genes and drive the continuing research forward pathogen-host interactions to explore the pathogenesis.